Intersectionality in Practice: How Public Transit Agencies Understand and Apply Intersectionality in the Pursuit of Gender Equity - Josephine Hazelton-Boyle (Journal of Social Equity and Public Administration)
Intersectionality offers public administrators great potential to understand the complex identities and lived experiences of the public and advance social equity. Conversations around intersectionality in public administration scholarship to date are primarily theoretical and have served an important role in introducing the concept to the field. However, gaps remain surrounding what it means for public administrators to apply an intersectional perspective to their work. This research builds on theoretical advancements to explore intersectionality in practice. Integrating a content analysis of all publicly available documents and websites posted by 129 U.S. public transit agencies with rich qualitative interviews with 45 U.S. public transit administrators, this research examines how transit administrators understand and apply intersectionality in the pursuit of gender equity. Findings from this research demonstrate specific areas in which transit administrators use intersectionality in their work to help create more equitable communities for all.